Anxious Futures: Capital, Nation and Advertising in Beirut, Lebanon - Callahan, Caitlin Alais (AUC Knowledge Fountain, 2024)
Contemporary billboard advertising in Beirut fuels anxiety in Beirut’s citizens. In a city suffering from daily uncertainties caused by a devastating financial collapse in 2019, and mourning victims of the worst non-nuclear explosion to ever occur in the Port of Beirut in 2020, Beirutis are also faced with advertising which constantly reinforces uneasiness. Visual advertisements market visas to leave the country, purchasing second passports and money counting machines, forming quotidian reminders of the current state of the country. Using interviews and visual ethnographic material collected during the summer of 2023, this thesis discusses how billboards help to foster dialogue around political and social commentary and advertise specific moral economies. It discusses the lived experience of Beirutis in a post-crisis economy, and how individuals adapt and cope within a constantly changing set of circumstances. It poses questions about what it means to be Lebanese in 2023 and examines the current state of citizenship and who is allowed to be a citizen.